Bioactive and nutritional potential of Alaria esculenta and Saccharina latissima - Afonso, C. (2021)
The brown seaweed species Alaria esculenta and Saccharina latissima are commercial edible resources in Norway. There are knowledge gaps regarding these species. Accordingly, they were characterized and their bioactivity and bioaccessibility evaluated. The fatty acid (FA) analysis revealed anω-3/ω-6 ratio of almost 2 in A. esculenta vs 1 in S. latissima. The FAs 18:4ω-3 (stearidonic acid) and 20:5ω-3 (eicosapentaenoic acid) were themain contributors to the relativeω-3 polyunsaturated FA richness in A. esculenta. This seaweed was also rich in fucoxanthin (66.1 ± 20.1 mg (100 g)−1 dw), representing approximately 4.1% of the total lipids. Hence, this species may be a source of natural fucoxanthin. Anti-inflammatory activity was significantly stronger (p < 0.001) in the ethanolic than in the aqueous extracts of the algal biomass, 48.3–60.4% vs 18.2–38.6% cyclooxygenase-2 (COX-2) inhibition. In the bioaccessible fraction of both species, phenolic content and antioxidant activitywere low.Moreover, the anti-inflammatory capacity was largely lost in this fraction, especially in the case of S. latissima. Regarding elemental composition, there were no large differences between the two brown seaweed species, being As levels high (53.11–58.93 mg kg−1 dw). However, this As is mostly organic and accordingly poses a lower risk to human health. The I content was high, especially in S. latissima, 2829 ± 58 mg kg−1 dw (557 ± 17 mg kg−1 dw in A. esculenta). Taking into account I levels, only 0.05 g and 0.39 g of S. latissima per day (based on I levels before digestion) are enough to reach I DRI and I TUIL, respectively, or 0.07 g and 0.57 g per day (based on I levels after digestion), for I DRI and I TUIL, respectively. The attained results point to an untapped potential regarding development of functional foods and other products with high-added value—particularly in the case of A. esculenta.